Selective detection of α4β1 integrin (VLA‐4)‐expressing cells using peptide‐functionalized nanostructured materials mimicking endothelial surfaces adjacent to inflammatory sites. Issue 5 (16th February 2018) - De Marco, Rossella; Greco, Arianna; Calonghi, Natalia; Dattoli, Samantha D.; Baiula, Monica; Spampinato, Santi; Picchetti, Pierre; De Cola, Luisa; Anselmi, Michele; Cipriani, Francesca; Gentilucci, Luca
Abstract: Persistent accumulation of immune cells mediated by α4β1 integrin (VLA‐4) is a hallmark of the inflammatory diseases and of chronic inflammation observed in the affected tissues of autoimmune diseases. Aiming at exploring new methods for monitoring the course of the inflammatory processes, we designed the first peptide‐functionalized nanostructured devices capable to mimic the high‐density multivalency binding between the α4β1 integrin‐expressing cells and the ligands overexpressed on the endothelial surfaces, in the proximity of the sites of inflammation. Specifically, we describe the first examples of monolayers constituted by dye‐loaded zeolite L crystals, coated with α4β1 integrin peptide ligands, and we analyze the adhesion of model Jurkat cells in comparison to non‐α4β1 integrin‐expressing cells. In particular, the peptidomimetic diphenylurea‐Leu‐Asp‐Val‐diamine allows significant and selective detection of α4β1 integrin‐expressing Jurkat cells, after very rapid incubation time, supporting the possible implementation in a diagnostic device capable to detect the desired cells from biological fluids, obtainable from patients in a noninvasive way. Abstract :